SCANNING ACOUSTIC FORCE MICROSCOPE MEASUREMENTS ON GRATING-LIKE ELECTRODES - Hesjedal, T; Chilla, E; Frohlich, H (1995)
Grating-like metal electrodes supplied with high- and low-frequency voltages were investigated by a Scanning Acoustic Force Microscope (SAFM). On piezoelectric LiNbO3, these electrodes form an interdigital transducer which generates surface acoustic waves according to the charge distribution on its electrodes when excited at a transducer's passband frequency. The influence of surface deformation and of surface charges on the cantilever deflection of the SAFM in contact and non-contact mode was systematically studied. Comparing the images of the electrodes which were prepared on piezoelectric and dielectric substrates, surface deformation and charge distributions were qualitatively separated. © 1995 Springer-Verlag.